2015
DOI: 10.3201/eid2110.150249
|View full text |Cite
|
Sign up to set email alerts
|

Cluster ofCryptococcus neoformansInfections in Intensive Care Unit, Arkansas, USA, 2013

Abstract: Use of short-term steroids was a risk factor for infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
0
13
0
6
Order By: Relevance
“…C. neoformans infections are rare in healthy adults; however, this fungal pathogen can cause complications in those with compromised immune systems (i.e., HIV patients) and can be acquired in a healthcare setting. 25 In kinetic kill experiments, N-arylated NH125 analogue 1 led to complete eradication of C. neoformans 66031 cells following 5 and 10 minute treatments at 50 μM (7-log reduction of viable fungal cells; Fig. 3A).…”
Section: Resultsmentioning
confidence: 92%
“…C. neoformans infections are rare in healthy adults; however, this fungal pathogen can cause complications in those with compromised immune systems (i.e., HIV patients) and can be acquired in a healthcare setting. 25 In kinetic kill experiments, N-arylated NH125 analogue 1 led to complete eradication of C. neoformans 66031 cells following 5 and 10 minute treatments at 50 μM (7-log reduction of viable fungal cells; Fig. 3A).…”
Section: Resultsmentioning
confidence: 92%
“…Clinical isolates from the six patients had three separate MLST patterns, suggesting either a point source consisting of multiple cryptococcus strains or an unknown non-point source. 57 The investigation revealed that short-term steroid use was associated with increased risk for cryptococcosis, which had not been previously described for this infection. 57 Thorough investigation of possible outbreaks of hospital-associated IFIs is needed to better understand their sources and to guide prevention measures.…”
Section: Health-care-associated Outbreaksmentioning
confidence: 73%
“…Furthermore, outbreaks often reveal emerging areas of concern that apply to IFIs in general. These topics include IFIs in new populations at risk due to factors such as travel or relocation, occupation, or immunosuppression; 37,39,57 IFIs associated with unusual events and sources such as natural disasters 43,45 and contaminated medications, often with unexpected pathogens; 68,71,72 and fungal pathogens appearing in geographic regions in which they have not been previously recognised. 22,31 …”
Section: Resultsmentioning
confidence: 99%
“…Lumbar puncture, therefore, was not performed. Hospital-acquired (48 h or more after admission) pulmonary cryptococcal infections are very rare, with only three cases found in a literature review (Table 1 ) [ 6 , 11 , 12 ]. All reported cases had chronic lung disease, which has been reported as a risk factor for cryptococcal infection [ 13 ].…”
Section: Discussionmentioning
confidence: 99%